2000
DOI: 10.1007/s004420050990
|View full text |Cite
|
Sign up to set email alerts
|

Effects of simulated grazing on different genotypes of Bouteloua gracilis : how important is morphology?

Abstract: Populations of grasses exposed to grazing by vertebrates often exhibit reduced stature, increased tillering, reduced flowering, and other morphological differences which distinguish them from ungrazed populations. These differences frequently are interpreted as an adaptive response that reduces grazing damage; however, there are few experimental tests of this hypothesis. This paper describes a field experiment designed to determine whether morphological variation among genotypes of the grass Bouteloua gracilis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 64 publications
2
32
0
Order By: Relevance
“…For example, under a fixed defoliation height the percentage of biomass removed would be higher in tall and erect phenotypes than in short and prostrate ones. Several papers studied the response of individual grasses to defoliation (Carman and Briske 1985;Jaramillo and Detling 1988;Oesterheld and McNaughton 1988;Detling 1988, 1990;Painter et al 1989;Briske and Anderson 1992;Jaindl et al 1994;Smith 1998;Kotanen and Bergelson 2000;Loreti et al 2001;Damhoureyeh and Harnett 2002). However, few have reported defoliation of the same shoot biomass proportion, and thus accurately evaluated defoliation tolerance (Briske and Anderson 1992;Damhoureyeh and Harnett 2002;Loreti et al 2001).…”
Section: Introductionmentioning
confidence: 95%
“…For example, under a fixed defoliation height the percentage of biomass removed would be higher in tall and erect phenotypes than in short and prostrate ones. Several papers studied the response of individual grasses to defoliation (Carman and Briske 1985;Jaramillo and Detling 1988;Oesterheld and McNaughton 1988;Detling 1988, 1990;Painter et al 1989;Briske and Anderson 1992;Jaindl et al 1994;Smith 1998;Kotanen and Bergelson 2000;Loreti et al 2001;Damhoureyeh and Harnett 2002). However, few have reported defoliation of the same shoot biomass proportion, and thus accurately evaluated defoliation tolerance (Briske and Anderson 1992;Damhoureyeh and Harnett 2002;Loreti et al 2001).…”
Section: Introductionmentioning
confidence: 95%
“…Previous studies already revealed that fertilization and defoliation can affect the genetic structure of populations (Kölliker et al 1998). Both the influence of grazing (Bühler and Schmid 2001;Kotanen and Bergelson 2000;Lennartsson et al 1997) and mowing (Billeter et al 2002;Kölliker et al 1998) have been studied in previous studies. However, much more can be learned about the impact of mowing than of grazing.…”
Section: Introductionmentioning
confidence: 96%
“…Thus if plants have traits that affect the probability of herbivore attack and if these traits have genetic variation within a plant population, then herbivores could act as selective agents on these traits. Recent studies on natural plant populations have revealed a considerable amount of genetic variation in susceptibility to herbivores (Roche and Fritz 1997;Kotanen and Bergelson 2000;Cronin and Abrahamson 2001), but also in plant traits likely affecting herbivore feeding. At least some species have genetic variation in these traits at scales of individual stands (Laitinen et al 2000) and thus relevant for food selection of individuals of the smaller herbivore species.…”
Section: Introductionmentioning
confidence: 99%